Enhancing university students' privacy literacy through an educational intervention: a Greek case-study. (20th November 2019) - Sideri, Maria; Kitsiou, Angeliki; Tzortzaki, Eleni; Kalloniatis, Christos; Gritzalis, Stefanos
Social network sites (SNSs) have doubtlessly altered the way that social actors communicate and interact worldwide. Several researches have shown that users disclose personal information within SNSs, while expressing privacy concerns. Users' inability to protect their privacy within SNSs, despite their recorded privacy concerns, constitutes the core of 'Privacy Paradox' and leads to privacy breaches or risks for themselves and other users. To reverse or at least minimise users' disclosure behaviour so as to protect themselves, researches underline the need for privacy awareness increase, focusing on the crucial role of education towards this. This research aims to explore the effects of a long-term university-based educational intervention for enhancing students' digital knowledge and skills to protect their privacy in SNSs efficiently. The findings are encouraging regarding students' privacy awareness enhancement and protection strategies adoption.